Rituximab Administration and Reactivation of HBV. (8th November 2010) - Tsutsumi, Yutaka; Ogasawara, Reiki; Kamihara, Yusuke; Ito, Shinichi; Yamamoto, Yoshiya; Tanaka, Junji; Asaka, Masahiro; Imamura, Masahiro
Abstract : Rituximab is a drug used for the treatment of B-cell non-Hodgkin's lymphoma, and its range of use has expanded to the treatment of collagen diseases such as idiopathic thrombocytopenic purpura and rheumatoid arthritis. One serious complication of rituximab use is the reactivation of dormant hepatitis B virus, and prevention of this phenomenon has become an urgent issue. This paper provides a general outline of the problem through an analysis of patient cases that we and other groups have experienced to date.